Technical-economic viability of mechanized picking coffee (Coffea arabica L.) in up to three annual operations - Oliveira, Bruno R. de [UNESP]; Tavares, Tiago de O. [UNESP]; Oliveira, Luan P. de [UNESP]; Silva, Rouverson P. da [UNESP]; Chicone, Livia C. G. (Spanish Natl Inst Agricultural & Food Research & Technolo, 2020)
Aim of study: Unavailability, coupled with the burden of labor for agricultural services nowadays, has made the mechanization process of harvesting of fallen coffee (Coffea arabica L.) essential. Although this operation has essential importance, it is often not monitored and executed in search of extreme quality. Considering the search for higher profits, this study aimed to analyze the performance of a coffee picker in three passes in an area in order to collect and process all the material and its economic viability. Area of study: The experiment was carried out in July 2017 in the Brazilian Cerrado, in the municipality of Presidente Olegario, Minas Gerais, Brazil, at Fazenda Gaucha/Cafe. Material and methods: The amount of gathered coffee was equivalent to 600 kg ha(-1) of processed coffee. The data from 2017 were used to analyze the economic viability of the picking operation. Treatments were distributed in split-blocks with three passes of the picking machine. The analyzed variables were picking and cleaning efficiency, picking losses, and percentage of vegetal and mineral impurities. Main results: Coffee losses reached the minimum level in the third pass. However, the harvesting operation could be carried out at most twice in the same area from the economic point of view under the evaluated conditions. Research highlights: Mechanized picking of coffee can be performed at most twice in the same area, providing a positive economic return.
Keywords: agricultural mechanization; picking viability; machine efficiency; coffee losses; economic analysis